Interactive effects of warming and water deficit on Shiraz vine transpiration in the Barossa Valley, Australia - Bonada, Marcos; Buesa, Ignacio; Morán, Martín A.; Sadras, Víctor O. (IVES, 2019)
Anticipating vineyard irrigation requirements in future climates is of strategic importance to maintain sustainability and wine regional identity. In the context of worldwide warming and climate-driven shifts in amount and seasonality of rainfall, we investigate the interactive effects of warming and water deficit on Shiraz vine transpiration under the conditions of the Barossa Valley, Australia. Transpiration of Shiraz vines was measured with thermal dissipation sap flow probes in a factorial experiment combining two thermal (heated with open-top chambers and control at ambient temperature) and two water regimes (wet and dry). Increased vapour pressure deficit (VPD) and canopy size in heated vines led to higher transpiration rates in irrigated vines during the first season. However, faster depletion of soil water by highly transpiring vines, followed by insufficient soil water replenishment by rain and irrigation, resulted in a negative feedback on vine transpiration the following season when heated vines were more water stressed than controls. The effect of warming was thus reversed the second season, with higher transpiration under ambient temperature. Therefore, dry soil, we suggest, could over-ride the effect of warming on the other variables driving transpiration (VPD, canopy size, and possibly stomatal conductance). Water scheduling will need to incorporate increased water demand under elevated temperature to maintain grapevine production in the long term.